Inheritance Distribution Practices in Ngadas Village Customary Law: Praktik Pembagian Warisan dalam Hukum Adat Desa Ngadas - Santriana, Agus; Purwaningsih, Sri Budi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Inheritance law in Indonesia reflects legal pluralism involving Islamic, Civil (BW), and customary systems.Specific Background: Ngadas Village, known for its strong customary traditions and mixed-religion population, applies local inheritance principles that differ from the Civil Code (BW).Knowledge Gap: Few studies have examined how these customary practices effectively prevent inheritance disputes.Aims: This research aims to analyze inheritance distribution in Ngadas Village through the perspective of customary and BW inheritance law.Results: The study found that inheritance distribution in Ngadas follows a bilateral kinship system, where assets are allocated equally during the testator’s lifetime to minimize disputes.Novelty: The integration of empirical and normative legal methods reveals the coexistence of traditional and state law principles.Implications: The findings emphasize the importance of community-based dispute resolution through consensus to maintain social harmony. Highlights: Customary inheritance reduces disputes in Ngadas Village. Bilateral kinship shapes inheritance distribution. Dispute resolution prioritizes consensus and tradition. Keywords: Inheritance Law, Customary Law, Ngadas Village, Kinship System, Dispute Resolution